The nexus of long noncoding RNAs, splicing factors, alternative splicing and their modulations - Pushkar Malakar; Sudhanshu Shukla; Meghna Mondal; Rajesh Kumar Kar; Jawed Akhtar Siddiqui (RNA Biology, 2024)
The process of alternative splicing (AS) is widely deregulated in a variety of cancers. Splicing is dependent upon splicing factors. Recently, several long noncoding RNAs (lncRNAs) have been shown to regulate AS by directly/indirectly interacting with splicing factors. This review focuses on the regulation of AS by lncRNAs through their interaction with splicing factors. AS mis-regulation caused by either mutation in splicing factors or deregulated expression of splicing factors and lncRNAs has been shown to be involved in cancer development and progression, making aberrant splicing, splicing factors and lncRNA suitable targets for cancer therapy. This review also addresses some of the current approaches used to target AS, splicing factors and lncRNAs. Finally, we discuss research challenges, some of the unanswered questions in the field and provide recommendations to advance understanding of the nexus of lncRNAs, AS and splicing factors in cancer.